Assessment of pain experience in adults and children after bracket bonding and initial archwire insertion - Marcio José da Silva Campos; Marcelo Reis Fraga; Nádia Rezende Barbosa Raposo; Ana Paula Ferreira; Robert Willer Farinazzo Vitral (Dental Press Editora, 2013)
INTRODUCTION: Ninety five percent of orthodontic patients routinely report pain, due to alterations in the periodontal ligament and surrounding soft tissues, with intensity and prevalence varying according to age. OBJECTIVE: This study aimed to assess toothache and buccal mucosal pain in adults and children during two initial phases of the orthodontic treatment. METHODS: The intensity of toothache and buccal mucosal pain reported by 20 patients, 10 children (11-13 years) and 10 adults (18-37 years) was recorded with the aid of a Visual Analog Scale (VAS), during 14 days - 7 days with bonded brackets only and 7 days with the initial archwire inserted. RESULTS: There was no significant difference in pain intensity among adults and children. After bracket bonding, 50% of the children and 70% of the adults reported pain. 70% of both groups reported pain after initial archwire insertion. While adults reported constant, low intensity, buccal mucosal pain, the children showed great variation of pain intensity, but with a trend towards decreasing pain during the assessment period. After initial archwire insertion the peaks of toothache intensity and prevalence occurred 24 hours in children and 48 hours in adults. CONCLUSIONS: In general, children reported pain less frequently than adults did, though with greater intensity.